Thyristor Voltage Transducer with Current Synchronization as Element of Automation Control System - A. S. Koval; В. Skaryna (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a model of «ТПН-АД» system which is controlled by non-current pause angle. It has been shown that thyristor voltage transducer being used in this case as an element of automation control system may be represented by an aperiodic element of the 1-st power. Its gain factor may be determined in accordance with the statistical characteristics of the thyristor voltage transducer itself.